2021
DOI: 10.1038/s41598-021-95876-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity and variety identification based on developed retrotransposon-based insertion polymorphism (RBIP) markers in sweet potato (Ipomoea batatas (L.) Lam.)

Abstract: Sweet potato, a dicotyledonous and perennial plant, is the third tuber/root crop species behind potato and cassava in terms of production. Long terminal repeat (LTR) retrotransposons are highly abundant in sweet potato, contributing to genetic diversity. Retrotransposon-based insertion polymorphism (RBIP) is a high-throughput marker system to study the genetic diversity of plant species. To date, there have been no transposon marker-based genetic diversity analyses of sweet potato. Here, we reported a structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Cluster analysis has been widely used for classifying plant genetic material. Dendrograms of the cluster analysis based on morphological and physiological traits for rice (Verma et al, 2019), tomato (Ayenan et al, 2021) and sweet potato (Meng et al, 2021). In this study, most traits of 149 cultivars showed significant differences.…”
Section: Discussion Evaluation Of Cultivated Potato Germplasm Resourcesmentioning
confidence: 57%
“…Cluster analysis has been widely used for classifying plant genetic material. Dendrograms of the cluster analysis based on morphological and physiological traits for rice (Verma et al, 2019), tomato (Ayenan et al, 2021) and sweet potato (Meng et al, 2021). In this study, most traits of 149 cultivars showed significant differences.…”
Section: Discussion Evaluation Of Cultivated Potato Germplasm Resourcesmentioning
confidence: 57%
“…The development of Retrotransposon-Based Insertion Polymorphism (RBIP) markers (Flavell et al, 1998) derived from sweet potatoes can determine intraspecific variability. These markers can also be used as core primer pairs for evaluating genetic diversity and constructing linkage maps of various plant species, guiding breeding and germplasm research (Meng et al, 2021). The RBIP marker was shown to be duplicated several times during the development of Asian pear cultivars and may provide a comprehensive picture of the complex relationship and evolution of Pyrus species (Jiang et al, 2015).…”
Section: Applications Of Ltr-retrotransposon As Molecular Marker Systemmentioning
confidence: 99%
“…Sweet potatoes may also be used for animal feed, starch extraction, alcohol, and biofuel. Many poor nations might benefit from the high concentration of β-carotene in these orange-fleshed sweet potatoes, which could help avoid blindness and maternal mortality caused by vitamin A insufficiency (Meng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%